2022
DOI: 10.1155/2022/5621665
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Acute Kidney Injury in Sub-Saharan African Adults: A Review of the Current Literature

Abstract: Acute kidney injury (AKI) is a complex condition that can occur in both community and hospital settings and has many aetiologies. These aetiologies may be infectious, toxic, surgical, or related to the different management methods. Although it is a major public health problem worldwide, it must be emphasised that both its incidence and mortality rate appear to be very high in sub-Saharan African (SSA) countries compared to developed countries. The profile of AKI is very different from that of more developed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 135 publications
0
12
0
Order By: Relevance
“…Acute kidney injury (AKI) is defined as a sudden and often reversible decline in kidney function. It is a common complication in hospitalized patients and is strongly associated with increased morbidity, mortality, and healthcare costs [ 1 , 2 ]. AKI is responsible for a high number of deaths in adults worldwide, especially as recent studies do not show a trend towards a decrease in the incidence and mortality [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Acute kidney injury (AKI) is defined as a sudden and often reversible decline in kidney function. It is a common complication in hospitalized patients and is strongly associated with increased morbidity, mortality, and healthcare costs [ 1 , 2 ]. AKI is responsible for a high number of deaths in adults worldwide, especially as recent studies do not show a trend towards a decrease in the incidence and mortality [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a common complication in hospitalized patients and is strongly associated with increased morbidity, mortality, and healthcare costs [ 1 , 2 ]. AKI is responsible for a high number of deaths in adults worldwide, especially as recent studies do not show a trend towards a decrease in the incidence and mortality [ 2 , 3 ]. The disease is underestimated due to difficulties in accessing care, lack of knowledge of the general demographics, and lack of blood tests in hospitals [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cause of AKI is often multifactorial with pre-existing comorbidities further increasing the risk [ 3 5 ], and include sepsis, volume depletion, nephrotoxic agents, major surgery, cardiogenic shock, complications with medications, hepato-renal syndrome, obstructive uropathy [ 5 – 8 ]. A recent meta-analysis by Kahindo et al reported that the common causes of AKI in adults in SSA were infections (28%), nephrotoxins (18%), pregnancy related (16%), glomerular disease (8%) and hypovolemia (5%) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%